High-intensity training for 1 month improves performance but not muscle enzyme activities in high-trained cyclists - Myburgh, K. H.; Lindsay, F. H.; Hawley, J. A.; Dennis, S. C.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 1995)
This study determined whether a sustained high-intensity interval training (HIT) program would change muscle enzyme activities and performance of six competitive cyclists. Baseline enzyme activities did not correlate with performance in these highly-trained Ss. Changes in performance were not related to enzyme alterations. Improved performance after one month of HIT in highly-trained Ss either precedes, or is unrelated to enhancement of muscle glycolytic and oxidative enzyme capacities. Implication: The notion that fitness levels reach a ceiling value in highly-trained athletes is supported by this study. Once that level is obtained, performance improvements have to come from resources other than further intense fitness work. It was shown that further improvements in performance levels of highly-trained cyclists resulted from factors that did not alter the conditioned, functioning state of muscles. Such factors, for example, could be skill improvements, increases in movement economy, and psychological focusing on only task-relevant variables.